Morphological and Fractal Characteristics of City Road Networks from Philippine Metropolitan Regions - Michelle Cirunay; Rene Batac (The Directorate for Research and Community Services, Institut Teknologi Bandung, 2022)
City road networks evolve from the fundamental need to connect various locations and to subdivide available space, especially in large urban areas. No two cities are exactly the same, however, and the differences manifest themselves in the layout of roads across their geographical regions. In this work, the fractal dimensions of urban roads from the three major metropolitan regions of the Philippines were investigated, along with the distributions of dimensionless spatial metrics for characterizing roads and road-bounded blocks. The dimensionless metrics reveal the commonalities, particularly the road and block motifs found in the urban road network tapestry. On the other hand, the fractal dimensions hint at the difference in levels of urbanization of the various cities and municipalities, which are considered subject to geographical constraints. This research adds to the growing literature with a complexity perspective on urban systems by reporting on an archipelagic road network data set. From a practical perspective, this work is deemed to be a useful first step towards an even deeper quantitative analysis of these regional economic centers and its insights may be used for drafting effective policy measures for management and further development.